Peningkatan Produksi Tanaman Bawang Daun (Allium Fistusolum) Melalui Aplikasi Pupuk Organik Cair Rumput Laut (Sargassum sp.) di Kota Wisata Batu - LENI, KADEK; FADIL, MOCH.; NIZAR, ACHMAD (Agrotrop : Journal on Agriculture Science, 2019)
The Effect of Providing Seaweed Liquid Organic Fertilizer (Sargassum sp) on The Growth and Production of Leaf Onion (Allium Fistusolum). Market demand for leaf onion has increased from year to year but the growth and production of leaf onion has not increased because the farmers always fertilize using chemical fertilizers. This study aims to determine the effect of seaweed liquid organic fertilizer on the growth and production of leaf onions. The study was conducted on a land area of 30m2 in Tulungrejo Village, Bumiaji, Batu - Malang. The experiment used CRD (Completely Randomized Design) with 5 treatments and 5 replications. The treatment carried out were without giving of seaweed liquid organic fertilizer on the leaves onion plant (P0), giving seaweed liquid organic fertilizer to the leaves onion plant with a concentration of 5 ml / liter (P1), 10 ml / liter (P2), 15 ml / liter (P3), and 20 ml / liter (P4). The parameters observed were plant height growth, growth in number of leaves and weight of harvesting leaf onion. Observation data were analyzed using analysis of variance level 5% and Duncan's advanced test at 5% level. The results showed that the application of seaweed liquid organic fertilizer had a significant effect on the growth of leaf onion plants and the production of onion leaf. On the growth of the number of leaves, the application of seaweed liquid organic fertilizer did not have a significantly effect on the leaf onion plants in the age of 63 days after planting.